Evaluasi Dampak Penggunaan Teknologi Augmented Reality dalam Storybook Interaktif Terhadap Literasi Sains Siswa SD - Ageng Sembodho; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the impact of using Augmented Reality (AR) technology in interactive storybooks on elementary students’ scientific literacy. The rapid development of digital technology requires innovative learning media to enhance students’ understanding, critical thinking, and problem-solving skills. This research employed a quantitative approach with a quasi-experimental design, specifically the Non-Equivalent Control Group Pretest–Posttest Design. The sample consisted of two groups of fifth-grade students at SDN Margorejo I/403 Surabaya, with 26 students in the experimental group and 26 students in the control group. Data were collected using scientific literacy tests (pretest and posttest) and student response questionnaires, and analyzed through N-Gain, normality, homogeneity, and Independent Samples t-test. The results showed that the experimental group achieved a higher improvement (N-Gain = 0.45, moderate category) compared to the control group (N-Gain = 0.22, low category). The hypothesis test indicated a significant difference (Sig. = 0.005 < 0.05), confirming that AR-based interactive storybooks significantly improve students’ scientific literacy. Additionally, questionnaire results revealed positive student responses, with high levels of motivation, interest, and engagement during learning. These findings suggest that integrating AR technology into interactive storybooks is an effective and innovative learning medium to support science education in elementary schools, despite challenges related to technological access and infrastructure.